Pretreatment Dietary Patterns, Serum Carotenoids and Tocopherols Influence Tumor Immune Response in Head and Neck Squamous Cell Carcinoma. (31st December 2021) - Argirion, Ilona; Arthur, Anna E.; Zarins, Katie R.; Bellile, Emily; Crowder, Sylvia L.; Amlani, Lahin; Taylor, Jeremy MG; Wolf, Greg T.; McHugh, Jonathan; Nguyen, Ariane; Mondul, Alison M; Rozek, Laura S.; et al.
Abstract: Background: Tumor infiltrating lymphocytes (TILs) aid in informing treatment for head and neck squamous cell carcinoma (HNSCC). Nevertheless, little is known about the role of diet on TILs. Methods: Immunohistologic expression of CD4, CD8, CD68, CD103, CD104 and FOXP3 were assessed in tissue microarrays from 233 previously untreated HNSCC patients. Associations between these markers and pretreatment dietary patterns were evaluated using linear regression. Associations between baseline serum carotenoids, tocopherols and TILs were assessed using logistic regression. Cox models evaluated the association between diet and TILs on overall and recurrence-free survival. Results: Consumption of a Western dietary pattern was associated with lower CD8+ and FOXP3+ infiltrates (p-value:0.03 and 0.02, respectively). Multivariable logistic regression models demonstrated significantly higher CD8+ (OR:2.21;p-value:0.001) and FOXP3+ (OR:4.26;p-value:<0.0001) among patients with high gamma tocopherol. Conversely, high levels of xanthophylls (OR:0.12;p-value:<0.0001), lycopene (OR:0.36;p-value:0.0001) and total carotenoids(OR:0.31;p-value: <0.0001) were associated with significantly lower CD68+. Among those with high CD4+ (HR:1.77;p-value:0.03), CD68+ (HR:2.42;p-value:0.004), CD103+ (HR:3.64;p-value:0.03) and FOXP3+ (HR:3.09;p-value:0.05), having a high Western dietary pattern increased the risk of overall mortality when compared to a low Western dietary pattern. Conclusion: Dietary patterns and serum carotenoids may play an important role in modifying TILs, and ultimately, outcome after diagnosis with HNSCC.